Implementación de un dispositivo electromecánico adaptable a cualquier accesorio fijo, para personas con discapacidad visual mediante las técnicas de ultrasonido y de posición global para mejorar el tiempo de su movilidad - Brborich Cortes, William Javier (2019)
The lack of an electromechanical device that allows the detection of obstacles, uneven terrain and determine their geospatial position for people with visual disabilities, had caused that individuals with this disability lose too much time tryinh to mobilize. For this reason, this dispositive was implemented, so people with this type of disability can move in less time. A bibliographic research was useful to support the idea. Also were take into account certain data to field research. The data found in the research contributed to the engineering. For the development of this object was necessary electronic design with programs such as Proteus, Fritzing it helped in the creation of the PCB and certain simulations made before manufacturing. In the mechanical software were used Solidwords for the design of elements such as pcb case, sensors and others. In addition the this the complete factorial design was used to locate the sensors in exact points and the inclination required to create a prototype. The methods mentioned before were important to improve the mobility time of blind people to move from one place to another.